Assessing delirium with nursing care instruments: Evaluation of the cognitive and associated domains. Issue 1 (February 2021) - Bode, Leonie; Fuchs, Simon; Gehrke, Samuel; Ernst, Jutta; Schubert, Maria; Nuñez, David Garcia; von Känel, Roland; Boettger, Soenke
Abstract: Objective: Nursing instruments have the potential for daily screening of delirium; however, they have not yet been evaluated. Therefore, after assessing the functional domains of the electronic Patient Assessment — Acute Care (ePA-AC), this study evaluates the cognitive and associated domains. Methods: In this prospective cohort study in the intensive care unit, 277 patients were assessed and 118 patients were delirious. The impacts of delirium on the cognitive domains, consciousness and cognition, communication and interaction, in addition to respiration, pain, and wounds were determined with simple logistic regressions and their respective odds ratios (ORs). Results: Delirium was associated with substantial impairment throughout the evaluated domains. Delirious patients were somnolent (OR 6), their orientation (OR 8.2–10.6) and ability to acquire knowledge (OR 5.5–11.6) were substantially impaired, they lost the competence to manage daily routines (OR 8.2–22.4), and their attention was compromised (OR 12.8). In addition, these patients received psychotropics (OR 3.8), were visually impaired (OR 1.8), unable to communicate their needs (OR 5.6–7.6), displayed reduced self-initiated activities (OR 6.5–6.9) and challenging behaviors (OR 6.2), as well as sleep–wake disturbances (OR 2.2–5), Furthermore, delirium was associated with mechanical ventilation, abdominal/thoracic injuries or operations (OR 4.2–4.4), and sensory perception impairment (OR 3.9–5.8). Significance of results: Delirium caused substantial impairment in cognitive and associated domains. In addition to the previously described functional impairments, these findings will aid the implementation of nursing instruments in delirium screening.